Analisis Penerimaan Pajak Reklame Guna Meningkatkan Pendapatan Asli Daerah Dibadan Pendapatan Daerah Kota Medan - Beny Sitakar; Wahyu Syarvina (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Research conducted at the Medan City Regional Tax and Retribution Management Agency aims to find out and analyze the actual value of advertising tax revenue with the aim of increasing Regional Original Income (PAD). This research also seeks to understand and analyze the causes of the decline in advertising tax revenues, as well as the factors that cause low taxpayer compliance. Using a descriptive approach, this research relies on interview findings and data regarding advertising tax targets and realization from 2014 to 2018. Data analysis involves surveys at research locations to collect information and draw conclusions, comparing identified problems with relevant theories to obtain support.The lack of contribution from advertising tax revenues to the Medan City Regional Tax Revenue and Retribution Agency is hampering the increase in PAD, due to low performance in achieving predetermined targets and the ineffectiveness of existing regulations. These regulations, especially those that limit the placement of advertisements, such as prohibiting sidewalks and roads and requiring the placement of advertisements on privately owned land, create obstacles for advertising businesses in obtaining location permits. The lack of taxpayer compliance is influenced by several factors such as weak enforcement and supervision of Satpol PP, limited awareness of advertisers, tax officers' inadequate efforts to interact with taxpayers, the large number of taxpayers who do not report, and public expectations regarding the solution. advertising tax arrears.